2020
DOI: 10.21542/gcsp.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension: From an orphan disease to a global epidemic

Abstract: [No abstract. Showing first paragraph of article]Pulmonary hypertension is a progressive disease characterized by an elevation of pulmonary artery pressure and pulmonary vascular resistance, leading to right ventricular failure and death. It remains a challenging chronic progressive disease, but the current interest and advent of medical therapy in the last 20 years has significantly changed the perception of medical community in this disease. Pulmonary hypertension is not a specific disease; the majority of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 187 publications
(141 reference statements)
0
7
0
1
Order By: Relevance
“…Pulmonary hypertension is increasingly considered to be a global disease 193 – 195 . Similarly, COVID-19 has affected all continents, including remote areas.…”
Section: Chronic Sequelae Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary hypertension is increasingly considered to be a global disease 193 – 195 . Similarly, COVID-19 has affected all continents, including remote areas.…”
Section: Chronic Sequelae Of Covid-19mentioning
confidence: 99%
“…The presence of endemic infections and polyparasitism has been identified as an important driver of pulmonary hypertension at the global level 193 , 194 , 223 . Many infectious diseases, in particular schistosomiasis, HIV infection and, potentially, tuberculosis, can induce pulmonary vascular diseases 207 210 by altering the Zinnate and adaptive immune response to COVID-19 (ref.…”
Section: Chronic Sequelae Of Covid-19mentioning
confidence: 99%
“…One such chemokine is CXCR4, which was found to be highly upregulated in the lungs of patients with COVID-19 ( Ackermann et al, 2020a ; Khalil et al, 2021 ). In addition, SARS-COV-2 viral proteins may interact with different types of cell surface receptors of pulmonary vasculature to induce upregulation of the p38 MAPK pathway ( Grimes and Grimes, 2020 ), VCAM-1 expression ( Birnhuber et al, 2021 ), nuclear factor–kappa B (NF-κB) translocation via the reduction of the dual-specificity phosphatases ( Goel et al, 2021 ), and up-regulation of the hypoxia-inducible factor–1α (HIF-1) ( Taniguchi-Ponciano et al, 2021 ), which, collectively, are implicated in the pathobiology of pulmonary vascular remodeling and dysfunction ( Butrous, 2020 ).…”
Section: The Role Of Sars-cov-2 In the Pathogenesis Of Pulmonary Vasc...mentioning
confidence: 99%
“…Pulmonary hypertension (PH) is defined as mean pulmonary artery pressure (PAP) at rest of >25 mmHg (1). It is divided into five major categories (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is divided into five major categories (2). Currently, one that is of particular clinical relevance is pulmonary arterial hypertension (PAH) (1). An internationally registered epidemiological data on PAH showed that the prevalence of PAH was 15 cases per million adults (2), making it a rare disease.…”
Section: Introductionmentioning
confidence: 99%